Motivation to Memorise the Qur'an at DFISQA Tahfizh House: Living Qur'an Studies - Junita, Junita; Akhmad Aidil Fitra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Variations on the Qur'an are growing and varied, giving rise to different responses. Including differences in accepting and functioning the verses of the Qur'an. Over time, the Qur'an is essentially a reading, reference and guidance understood and interpreted differently among the community according to the knowledge they have. As the DFISQA Tahfizh House which revives the Qur'an through motivation. The holy verse of the Qur'an which is used as the basis for the jargon of enthusiasm in memorising the Qur'an is surah al-Qamar verse 17. This article aims to examine how surah al-Qamar verse 17 is used as motivation by DFISQA Tahfizh House students in memorising the Qur'an. This article uses qualitative research with a phenomenological approach. Phenomenology intends to explore the motivation of DFISQA Tahfizh House students towards Surah al-Qamar verse 17 in memorising the Qur'an. The results of this research show: First, Surah al-Qamar verse 17 is generally known as a verse that explains Allah's guarantee of ease in memorising the Qur'an. as done by the students of the DFISQA Tahfizh House. Santri perceive, understand and practice what is in the verse as a reference and motivation in memorising the Qur'an and then manifested in the form of istiqomah to increase memorisation. Second, the meaning resulting from the acceptance of DFISQA Tahfizh House students of surah al-Qamar verse 17 is to increase enthusiasm in memorising the Qur'an, increase awareness of memorising the Qur'an, and as a solace when facing difficulties in memorising the Qur'an.